Multimedia quality of experience (QoE) : current status and future requirements - Dagiuklas, Tasos (Wiley, 2015)
"This book discusses the current status of QoE research; reporting latest advances from various standardisation bodies (ITU, ETSI, IEEE, IETF) Multimedia Quality of Experience (QoE): Current Status and Future Requirements discusses the current status of QoE (Quality of Experience) research, providing guidelines on QoE assessment and management practice. Moreover, the book covers many different aspects of QoE research, including definition, standardization (ITU, ETSI, IEEE, IETF, etc.), measurement, management, and architectures. In addition, the authors bring together contributions from recognized experts (worldwide) in the area of subjective and objective QoE video assessment. Topics/chapters include: (1) QoE Definition and its relation/mapping to QoS; QoE Standardization activities; QoE Metrics for various media applications; QoE Subjective and Objective Evaluation Methodologies; QoE Control, Monitoring and Management strategies; End-to-End QoE Architectures in heterogeneous environments. Discusses the current status of QoE research; reporting latest advances from various standardisation bodies (e.g. ITU, ETSI, IEEE, IETF) Provides guidelines on QoE assessment and management practice Explores methods, means and architectures of QoE Addresses multiple technologies and requires input from multiple disciplines such as engineering, sociology and psychology Brings together contributions from recognized experts (worldwide) in the area of subjective and objective QoE video assessment Considers future requirements of QoE "--